2019 International Joint Conference on Neural Networks (IJCNN) 2019
DOI: 10.1109/ijcnn.2019.8852184
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Group Cohesiveness in Images

Abstract: The cohesiveness of a group is an essential indicator of the emotional state, structure and success of a group of people. We study the factors that influence the perception of grouplevel cohesion and propose methods for estimating the humanperceived cohesion on the group cohesiveness scale. In order to identify the visual cues (attributes) for cohesion, we conducted a user survey. Image analysis is performed at a group-level via a multi-task convolutional neural network. For analyzing the contribution of facia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Furthermore, Treadwell et al [9] created GCS (shown in Fig. 1) to evaluate cohesiveness among group members based on a 4-point scale of strongly disagree (SD), disagree (D), agree (A) and strongly agree (SA), or can be represented by numbers from 0 to 3, correspondingly [10]. These studies have formed the fundamental knowledge for the evolution of social psychology especially, group cohesiveness.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, Treadwell et al [9] created GCS (shown in Fig. 1) to evaluate cohesiveness among group members based on a 4-point scale of strongly disagree (SD), disagree (D), agree (A) and strongly agree (SA), or can be represented by numbers from 0 to 3, correspondingly [10]. These studies have formed the fundamental knowledge for the evolution of social psychology especially, group cohesiveness.…”
Section: Related Workmentioning
confidence: 99%
“…This is one of the first studies that utilizes machine learning to predict group cohesion of a group of people in videos. Recently, the EmotiW 2019 presented the first study of group cohesion prediction in statics images [10,11]. The EmotiW organizers provided a database for group cohesion, which is an upgrade version of Group Affect Database (GAF 3.0) [20] with group cohesion labels (GAF-Cohesion).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Ghosh et al proposed methods to automatically predict group cohesiveness in images from the GAF 3.0 dataset, focusing on facial expressions [54]. Their approach achieves near human-level performance in predicting a group's cohesion score, but this mainly concerns perceived cohesion and does not provide any insight on the underlying behavioral dynamics of cohesion.…”
Section: ) Automated Approaches To Detect Cohesionmentioning
confidence: 99%